Synthesis of 6-epi- and 4,6-bisepi-N-acetyl-D-neuraminic acid by aldol condensation - Mack, Hans; Brossmer, Reinhard (Tetrahedron letters, 1992)
Reaction of allofurano-2, 3-oxazoline 2 with potassium ditert. butyl oxaloacetate afforded the two diastereomeric compounds 3 and 3a which, after deblocking and alkaline treatment, are converted to the two epimeric sialic acids 5 and 5a.
Elektronische Reproduktion der Druck-Ausgabe 7. März 2002
Gesehen am 25.06.2024